LEXICAL AND SEMANTIC FEATURES OF ADOLESCENT COMMUNICATION (BASED ON ENGLISH-LANGUAGE INTERNET BLOGS) - Borymska, Oksana (Global Prosperity, 2021)
The study aims to determine the phenomenon of newly created lexical and semantic units in the media space of social networks Instagram, Tik-Tok and Clubhouse, inherent in the adolescent audience; identifying the reasons for the formation of new slang words, their analysis, the impact on the modern language space. The article’s core is the classification of these language units according to thematic groups, determining their emotional component. The material for the study was slang lexical items that are pretty popular among young users of social networks in the modern media space. The language of Internet communications is a broad field for linguistic and sociological research in general. The author agrees that the means of language can reflect the social status of adolescents, their views, and worldview in the media. Blogs on the Internet create an artificial virtual field for self-expression and communication. It is concluded that the research topic has a vast field for further in-depth research.